2018
DOI: 10.1080/13854046.2018.1482003
|View full text |Cite
|
Sign up to set email alerts
|

Detection of symptom over-reporting on the Neurobehavioral Symptom Inventory in OEF/OIF/OND veterans with history of mild TBI

Abstract: Both the NSI Total and Validity-10 cut scores consistently identified potential symptom exaggeration across three mild TBI samples. Clinicians and researchers who use the NSI are encouraged to utilize either embedded validity measure in their practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…For example, Lange, Brickell, Lippa, and French (2015) examined military personnel and how well the NSI validity scales differentiated between groups based on valid or invalid performance on the PAI; the Validity-10 outperformed the other two scales, with optimal cutoffs ranging from 19 to 28 depending on degree of confidence. Similarly, Bodapati et al (2019) examined the NSI validity scales in a veteran sample and reported that Validity-10 cutoffs ranging between 22 and 27 optimally discriminated between valid and invalid groups based on the MMPI-2-RF.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Lange, Brickell, Lippa, and French (2015) examined military personnel and how well the NSI validity scales differentiated between groups based on valid or invalid performance on the PAI; the Validity-10 outperformed the other two scales, with optimal cutoffs ranging from 19 to 28 depending on degree of confidence. Similarly, Bodapati et al (2019) examined the NSI validity scales in a veteran sample and reported that Validity-10 cutoffs ranging between 22 and 27 optimally discriminated between valid and invalid groups based on the MMPI-2-RF.…”
Section: Resultsmentioning
confidence: 99%
“…The total score with a cutoff of >58 was initially presented with a sensitivity of .79 and .59 in development and clinical samples (Vanderploeg et al, 2014), respectively. The total score was evaluated in only two additional studies in the VA (Table 7), with recommended cutoffs ranging from ≥51 to ≥67 (Ashendorf, 2019;Bodapati et al, 2019). Both of these prior studies used similar samples to ours (VA Iraq/ Afghanistan veteran sample, mild TBI), though both prior studies used the MMPI-2-RF as the criterion.…”
Section: Discussionmentioning
confidence: 99%
“…The first aim of this article was to validate the NSI SVTs and mBIAS using the SIMS as a validity criterion. Prior studies have predominantly used the MMPI-2/RF (Armistead-Jehle et al, 2018; Ashendorf, 2019; Bodapati et al, 2019; Lange et al, 2015; Lippa et al, 2016) or the PAI (Vanderploeg et al, 2014) validity scales as an external criterion. The SIMS is a stand-alone SVT with five subscales created to sample overreporting of neurological, affective, psychotic, intellectual, and amnestic symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations